Proteomic Analysis of Cell Walls of Two Developmental Stages of Alfalfa Stems - Verdonk, Julian C.; Hatfield, Ronald D.; Sullivan, Michael L. (Frontiers in Plant Science, 2012)
Cell walls are important for the growth and development of all plants. They are also valuable resources for feed and fiber, and more recently as a potential feedstock for bioenergy production. Cell wall proteins comprise only a fraction of the cell wall, but play important roles in establishing the walls and in the chemical interactions (e.g., crosslinking) of cell wall components. This crosslinking provides structure, but restricts digestibility of cell wall complex carbohydrates, limiting available energy in animal and bioenergy production systems. Manipulation of cell wall proteins could be a strategy to improve digestibility. An analysis of the cell wall proteome of apical alfalfa stems (less mature, more digestible) and basal alfalfa stems (more mature, less digestible) was conducted using a recently developed low-salt/density gradient method for the isolation of cell walls. Walls were subsequently subjected to a modified extraction utilizing EGTA to remove pectins, followed by a LiCl extraction to isolate more tightly bound proteins. Recovered proteins were identified using shotgun proteomics. We identified 272 proteins in the alfalfa stem cell wall proteome, 153 of which had not previously been identified in cell wall proteomic analyses. Nearly 70% of the identified proteins were predicted to be secreted, as would be expected for most cell wall proteins, an improvement over previously published studies using traditional cell wall isolation methods. A comparison of our and several other cell wall proteomic studies indicates little overlap in identified proteins among them, which may be largely due to differences in the tissues used as well as differences in experimental approach.